Community Empowerment through the Application of Tut Wuri Handayani to Organizational Leaders in Indonesia and Malaysia - Ignasius Soni Kurniawan; Umi Wahidah; Ana Fitrotun Nisa; Tri Ratna Purnamarini (Universitas Muhammadiyah Palembang, 2024)
These activities aims to provide an explanation of the application of Tut Wuri Handayani to SME leaders in Yogyakarta consisting of SMEs Pottery & Ceramic Crafts